2019
DOI: 10.1002/2211-5463.12696
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated polysaccharides interact with fibroblast growth factors and protect from denaturation

Abstract: Fibroblast growth factors (FGFs) regulate embryonic development and homeostasis, including tissue and organ repair and specific aspects of metabolism. The basic FGF and acidic FGF, now known as FGF2 and FGF1, are widely used protein drugs for tissue repair. However, they are susceptible to denaturation at ambient temperatures and during long‐time storage, which will reduce their biological activity. The interaction of FGFs with the sulfated domains of heparan sulfate and heparin is essential for their cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
2
22
1
Order By: Relevance
“…We applied fucoidan as a free molecule in solution to the cell culture systems, whereas a lot of studies investigated the bioactivity of fucoidans incorporated in a delivery system. As reported for other sulfated sugars [ 41 , 42 ], also fucoidans seem to be able to bind growth factors like VEGF and their receptors. Supporting the assumption that fucoidans are able to bind to VEGF, we showed in an ELISA-based competitive binding assay that the tested extracts suppress the binding of VEGF to its antibody in a concentration-dependent manner ( Figure S1 ).…”
Section: Discussionsupporting
confidence: 59%
“…We applied fucoidan as a free molecule in solution to the cell culture systems, whereas a lot of studies investigated the bioactivity of fucoidans incorporated in a delivery system. As reported for other sulfated sugars [ 41 , 42 ], also fucoidans seem to be able to bind growth factors like VEGF and their receptors. Supporting the assumption that fucoidans are able to bind to VEGF, we showed in an ELISA-based competitive binding assay that the tested extracts suppress the binding of VEGF to its antibody in a concentration-dependent manner ( Figure S1 ).…”
Section: Discussionsupporting
confidence: 59%
“…In a previous study, heparin and dextran sulfate were reported to protect bFGF from denaturation [ 9 ], and the effective lowest protecting concentration for 5 μM of bFGF was reported as 5–25 μg/mL. In our results, the effective concentration of the dextran sulfate for cell proliferation was 25 ng/mL in a medium containing 60 ng/mL (3.5 nM, FW 17,000) of bFGF.…”
Section: Discussionsupporting
confidence: 54%
“…It is also recommended that these media should be stored at 4 °C after the addition of supplements to the basal media, and be used within 1 week. Considerable efforts have been made in the delivery and formulation of bFGF and other proteins to stabilize them for therapeutic purposes [ [9] , [10] , [11] ], but there has been limited research on stabilizing bFGF in the cell culture media.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the heparin stabilizes the FGF-2-FGFR-1 complex, promoting receptor dimerization and thereby facilitating GF signal transduction [ 277 ]. The protection afforded by binding to heparin extends to other sulfated polysaccharides as well, including sulfonated dextran, dextran sulfate, lambda -carrageenan, and chondroitin sulfate [ 262 , 278 ]. Heparin has similar effects on other growth factors.…”
Section: Biomedical Applicationsmentioning
confidence: 99%